ADJECTIVE. TYPES OF ADJECTIVE. DEGREES OF ADJECTIVE - Imomnazarova Xurriyat; Pardayev Utkir (PEDAGOGS, 2024)
Adjectives are one of the main parts of English grammar and have a wide scope. That is, adjectives are almost never used after verbs. But there are such verbs that we can easily use adjectives after them. There are adjectival suffixes such as “ing” and “ed”, whose meanings are close to each other and more difficult to distinguish, and it is a mistake to substitute one for the other. Adjectives are divided into types according to meaning, structure, and form. The deeper one studies this category, the more meanings emerge.